Lithium supplement material and preparation method thereof, positive electrode material and secondary battery
By covering the two -layer covering structure of organic inorganic hybrid materials and acid inert materials on the surface of lithium -rich materials, the problem of gases of lithium -rich materials during high temperature aging is solved, and the stability and life of the battery are improved.
Patent Information
- Application Number
- CN202411758424.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-01-24
AI Technical Summary
Existing lithium-rich materials are prone to side reactions with the electrolyte during the high-temperature aging stage of secondary batteries, resulting in gas generation and battery bloating, mainly due to the excessive amount of residual alkali on the surface.
By covering the first cover layer and the second cover layer of the outer layer of lithium -enriched materials, the first cover layer is composed of organic inorganic hybrid materials. The layer can effectively eliminate the alkali on the surface of the lithium -rich material and prevent the erosion of hydrofluoric acid in the electrolyte.
It effectively reduces the gas production of lithium-rich materials in the battery, improves the chemical stability and air stability of the battery, reduces side reactions during high-temperature aging, and extends the service life of the battery.
Smart Images

Figure CN119361712A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery. Background Art
[0002] The rapid development of electric vehicles and electrochemical energy storage technology has put forward higher requirements for battery energy density, and the limitations of traditional lithium-ion batteries in energy density have become increasingly prominent. One of the keys to improving battery energy density is to improve the Coulombic efficiency of the anode, because compared with the cathode, the anode will experience significant lithium loss in the initial cycle, mainly due to the formation of the solid electrolyte interface (SEI) and the electroplating of metallic lithium. Therefore, the development of pre-lithiation technology to compensate for this loss of active lithium has become the focus of improving the energy density of the whole battery.
[0003] In the pre-lithiation technology, adding lithium-rich materials to the positive electrode for lithium supplementation has been widely studied. However, the existing lithium-rich materials have exposed obvious defects in the high-temperature aging stage of the battery. Because the residual alkali on the surface of the lithium-rich material is too high, the lithium-rich material is prone to side reactions with the electrolyte, thereby generating gas and causing the battery to swell. Therefore, how to reduce the residual alkali on the surface of the lithium-rich material to reduce gas production has become the key. Summary of the invention
[0004] The purpose of the present application is to provide a lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery, so as to solve the problems of residual alkali on the surface of the secondary battery and high gas production.
[0005] To achieve the purpose of this application, this application provides the following technical solutions:
[0006] In a first aspect, the present application provides a lithium-supplementing material, comprising a core, a first coating layer and a second coating layer, wherein the first coating layer is coated on the outer layer of the core, and the second coating layer is coated on the outer layer of the first coating layer, the core comprises a lithium-rich material, the first coating layer comprises an organic-inorganic hybrid material, the second coating layer comprises an acid-inert material, and the second coating layer is a continuous coating layer.
[0007] In one embodiment, the precursor of the organic-inorganic hybrid material includes a first coupling agent, the precursor of the acid-inert material includes a second coupling agent, and the density of the first coating layer is greater than the density of the second coating layer.
[0008] In one embodiment, the lithium supplement material further includes conductor particles, the conductor particles are bonded to the outer surface of the inner core, the first coating layer is bonded to the conductor particles, and the first coating layer and the conductor particles together fully coat the inner core.
[0009] In one embodiment, there are a plurality of the conductor particles, and the plurality of the conductor particles are independently distributed on the outer surface of the inner core to form an island-shaped coating, and the first coating layer is combined between the plurality of the conductor particles and connected to the outer surface of the inner core.
[0010] In one embodiment, the particle size of the conductor particles is greater than or equal to the thickness of the first coating layer, and at least a portion of the outer surface of the conductor particles is connected to the second coating layer.
[0011] In one embodiment, the mass proportion of the organic-inorganic hybrid material in the lithium supplementing material is 0.2% to 2%.
[0012] In one embodiment, the acid-inert material accounts for 0.2% to 2% by mass of the lithium-supplementing material.
[0013] In one embodiment, the mass proportion of the conductor particles in the lithium supplement material is 0.5% to 2%.
[0014] In one embodiment, the thickness of the first coating layer is 10 nm-100 nm.
[0015] In one embodiment, the thickness of the second coating layer is 10 nm-100 nm.
[0016] In one embodiment, the particle size of the conductor particles is 20 nm-800 nm.
[0017] In a second aspect, the present application provides a method for preparing a lithium-supplementing material, comprising: evenly mixing a lithium-rich material and an organic-inorganic hybrid material precursor and sintering them so that the organic-inorganic hybrid material is coated on the outer layer of the lithium-rich material to form a first coating layer; mixing the lithium-rich material having the first coating layer with an acid-inert material precursor and drying them so that the acid-inert material is coated on the outer layer of the first coating layer to form a continuously coated second coating layer, thereby obtaining a lithium-supplementing material.
[0018] In one embodiment, the step of uniformly mixing the lithium-rich material and the organic-inorganic hybrid material precursor and sintering the mixture further includes: uniformly mixing the lithium-rich material and conductor particles and sintering the mixture so that the conductor particles are bonded to the outer surface of the lithium-rich material.
[0019] In a third aspect, the present application provides a positive electrode material, which includes an active material and the lithium-supplementing material as described in the first aspect, or includes a lithium-supplementing material obtained by the preparation method of the lithium-supplementing material as described in the second aspect.
[0020] In a fourth aspect, the present application provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode and the negative electrode are arranged in the electrolyte, and the positive electrode comprises the positive electrode material as described in the third aspect.
[0021] The present application optimizes the surface structure of the lithium-rich material, and coats the first coating layer and the second coating layer on the outer surface of the lithium-rich material. The two-layer coating can protect the lithium-rich material. Among them, the first coating layer includes an organic-inorganic hybrid material, which can be used to eliminate the residual alkali on the surface of the lithium-rich material, and the organic-inorganic hybrid material can build a preliminary outer layer protection, improve the chemical stability and air stability of the lithium-rich material, and inhibit the excessive internal resistance and open circuit energy barrier of the lithium-rich material, and can also reduce external water vapor erosion. Furthermore, the second coating layer includes an acid-inert material, which can form a protective outermost layer to prevent and inhibit the erosion of the lithium-rich material by hydrofluoric acid in the electrolyte, thereby reducing the gas production of the lithium-rich material in the electrolyte; and after the lithium-supplemented material is made into a battery, the acid-inert material can be used as a battery additive, because the trace water in the battery causes the acid-inert material to hydrolyze slightly, and some acid-inert material groups enter the electrolyte to protect the electrolyte solvent. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 is a schematic cross-sectional view of a lithium supplement material according to an embodiment;
[0024] Figure 2 is a cross-sectional schematic diagram of a lithium supplement material according to another embodiment;
[0025] Figure 3 is a cross-sectional schematic diagram of a lithium supplement material according to another embodiment;
[0026] Figure 4 is a flow chart of a method for preparing a lithium supplement material according to an embodiment;
[0027] Figure 5 is a transmission electron microscope image (TEM) of the lithium supplement material in Example 1;
[0028] Figure 6 is a scanning electron microscope image (SEM) of the lithium supplement material in Example 1;
[0029] Figure 7 is a scanning electron microscope (SEM) image of the lithium supplement material in Example 1 at another viewing angle;
[0030] Figure 8is a scanning electron microscope (SEM) image of the lithium supplement material in Example 1 at another viewing angle;
[0031] Fig. 9 is the Raman image of the lithium-supplemented material of Example 1 and the lithium-rich material of Comparative Example 1;
[0032] Fig.10 It is the infrared image of the lithium supplement material of Example 1 and the lithium rich material of Comparative Example 1. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0034] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.
[0035] It should be noted that the "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] All steps of the present application can be carried out sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) carried out sequentially, or may also include steps (b) and (a) carried out sequentially. For example, when it is mentioned that the method may further include step (c), it means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or may also include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0037] The following will describe in detail some embodiments of the present application with reference to the accompanying drawings. Without conflict, the following embodiments and the features in the embodiments can be combined with each other.
[0038] The present application provides a lithium supplement material. Please refer to Figure 1-Figure 3 .
[0039] In one embodiment, please refer to Figure 1 , the lithium supplement material includes a core 10, a first coating layer 20, and a second coating layer 30. The first coating layer 20 is coated on the outer surface of the core 10, and the second coating layer 30 is coated on the outer surface of the first coating layer 20. The core 10 includes a lithium-rich material, the first coating layer 20 includes an organic-inorganic hybrid material, the second coating layer 30 includes an acid-inert material, and the second coating layer 30 is a continuous coating layer.
[0040] In one embodiment, the chemical formula of the lithium-rich material includes Li x1 M y1 O z1 , where M is at least one element among Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, etc., 1≤x1≤8, 0<y1, 0<z1<7. In a specific embodiment, the lithium-rich material may include at least one of Li5FeO4, Li6MnO4, Li6CoO4, Li6ZnO4, Li2NiO2, Li2CuO2, Li2CoO2, Li2MnO2, Li2Ni 0.5 Mn 1.5 O4, Li2Ni d Cu (1-d) O2 (0<d<1), etc.
[0041] In one embodiment, the chemical formula of the lithium-rich material includes Li 1+x2 A y2 O z2, where 0 <x2≤1.2,1≤y2<3,z2> 0, A includes at least one of Ni, Fe, Mn, Co, Cr, V, Mo, Ti, Nb, Zr, Cu, and Mg. These lithium-rich materials can be used as lithium supplements or directly as positive electrode materials. Exemplarily, the lithium-rich material includes at least one of Li2CuO2, Li2NiO2, and Li2MnO2.
[0042] In one embodiment, the lithium-rich materials mentioned above may be undoped or modified by doping, or may be surface coated, pre-lithiated, etc. These lithium-rich materials have high theoretical capacity and structural stability, can provide abundant lithium ions, effectively supplement the irreversible lithium ions consumed by the formation of SEI film at the negative electrode, and improve the initial efficiency and overall electrochemical performance of the battery.
[0043] In one embodiment, the present application is to eliminate the residual alkali on the surface of the above-mentioned lithium-rich material, and reduce the material resistance to prevent external water vapor erosion. The present application coats the surface of the inner core 10 of the lithium-rich material with a first coating layer 20 and a second coating layer 30. The first coating layer 20 includes an organic-inorganic hybrid material, and the first coating layer 20 is an organic-inorganic hybrid film layer formed by the organic-inorganic hybrid material. The first coating layer 20 is continuously coated on the outer surface of the inner core 10, which can eliminate the residual alkali on the surface of the lithium-rich material, reduce the resistance of the lithium-rich material, and prevent external water vapor erosion.
[0044] In one embodiment, the second coating layer 30 includes an acid-inert material, and the second coating layer 30 is coated outside the first coating layer 20, and the second coating layer 30 can also form a continuous coating. It should be explained that the acid-inert material refers to a material that has high stability in an acidic environment and can maintain the stability of the electrolyte, and in a slightly acidic electrolyte, some acid-inert materials can also react with hydrogen fluoride (HF) in the electrolyte to maintain the stability of the electrolyte environment. Therefore, the second coating layer 30 can prevent and inhibit the corrosion of the lithium-rich material by hydrofluoric acid in the electrolyte, thereby reducing the gas production of the lithium-rich material in the electrolyte; and after the lithium-supplemented material is made into a battery, the acid-inert material can be used as a battery additive, because the trace water in the battery causes the acid-inert material to be slightly hydrolyzed, and some acid-inert material groups enter the electrolyte to protect the electrolyte solvent.
[0045] It should be explained that the composition of the electrolyte (especially the electrolyte) in the battery is rich. During the heat generation stage of the battery, the high temperature will cause the electrolyte to produce harmful components (especially hydrofluoric acid). Hydrofluoric acid will destroy the interface between the electrode material and the electrolyte in terms of structure and composition, thereby causing side reactions to produce gases such as H2, CO, CO2, C2H4, and side reactions of the undecomposed products of the lithium supplementing material to produce O2. The surface of the lithium supplementing material in this application has an acid-inert material, which can not only protect the lithium-rich material from being eroded by hydrofluoric acid, but also the acid-inert material that is slightly hydrolyzed can protect the electrolyte components, ultimately achieving the purpose of reducing battery gas production.
[0046] The present application optimizes the surface structure of the lithium-rich material, and coats the first coating layer 20 and the second coating layer 30 on the outer surface of the lithium-rich material. The two-layer coating can protect the lithium-rich material. Among them, the first coating layer 20 includes an organic-inorganic hybrid material, which can be used to eliminate the residual alkali on the surface of the lithium-rich material, and the organic-inorganic hybrid material can build a preliminary outer layer protection, improve the chemical stability and air stability of the lithium-rich material, and inhibit the excessive internal resistance and open circuit energy barrier of the lithium-rich material, and can also reduce external water vapor erosion. Furthermore, the second coating layer 30 includes an acid-inert material, which can form a protective outermost layer to prevent and inhibit the corrosion of the lithium-rich material by hydrofluoric acid in the electrolyte, thereby reducing the gas production of the lithium-rich material in the electrolyte; and after the lithium-supplemented material is made into a battery, the acid-inert material can be used as a battery additive, because the trace water in the battery causes the acid-inert material to hydrolyze slightly, and some acid-inert material groups enter the electrolyte to protect the electrolyte solvent.
[0047] In one implementation, please refer to Figure 1 , the precursor of the organic-inorganic hybrid material includes a first coupling agent, and the precursor of the acid-inert material includes a second coupling agent. Specifically, the precursor of the organic-inorganic hybrid material can be a first coupling agent, and the coupling agent coated on the lithium-rich material is sintered so that the first coupling agent can be partially converted into an inorganic material (such as silicon dioxide), thereby obtaining an organic-inorganic hybrid material, in which an O-Si-O bond is included. The O-Si-O bond improves the stability of the organic-inorganic hybrid material, can eliminate residual alkali on the surface of the material, and reduce resistance to prevent water vapor erosion. In addition, the precursor of the acid-inert material includes a second coupling agent, and the types of the first coupling agent and the second coupling agent can be the same or different.
[0048] In one embodiment, the first coupling agent or the second coupling agent includes one or more of a phosphate coupling agent, a silane coupling agent, an aluminate coupling agent, a titanate coupling agent, and a chromium complex coupling agent. It should be noted that the present application uses a coupling agent as a precursor to coat the lithium-rich material, on the one hand to avoid the erosion of the lithium-supplementing material by external water vapor during the production and transportation process; on the other hand, after the lithium-supplementing material is made into a battery, the acid-inert material can be used as a battery additive, because the trace water in the battery causes the coupling agent groups in the acid-inert material to be slightly hydrolyzed, and part of the coupling agent groups enter the electrolyte to protect the electrolyte solvent, and the attack of hydrofluoric acid is resisted by the residual coupling agent groups.
[0049] In one embodiment, the density of the first coating layer 20 is greater than the density of the second coating layer 30. It is understood that both the first coating layer 20 and the second coating layer 30 are prepared by a coupling agent, but the organic-inorganic hybrid material in the first coating layer 20 is obtained by sintering and converting the coupling agent, and the density of the coupling agent is increased after sintering, so that the first coating layer 20 forms a dense coating layer. Therefore, the first coating layer 20 has a more stable property than the second coating layer 30, which can not only eliminate residual alkali, but also prevent external water vapor erosion.
[0050] In one implementation, please refer to Figure 2 The lithium-supplementing material further includes a conductor particle 40, the conductor particle 40 is bonded to the outer surface of the core 10, the first coating layer 20 is bonded to the conductor particle 40, and the first coating layer 20 and the conductor particle 40 together fully coat the core 10. Specifically, the conductor particle 40 is used to improve the cross-sectional stability of the lithium-rich material, and the conductor particle 40 may have ion-conducting properties and electron-conducting properties. The conductor particle 40 is bonded to the outer surface of the core 10, and the first coating layer 20 and the second coating layer 30 may be bridged by the conductor particle 40 and coated on the outer surface of the lithium-rich material. In a specific embodiment, the conductor particle 40 includes a phosphate.
[0051] In the present application, by setting conductor particles 40 on the outer surface of the lithium-rich material, the conductor particles 40 can be used to react with the residual alkali on the surface of the lithium-rich material to achieve the purpose of eliminating the residual alkali and preliminarily construct a first protective layer; and then by setting a first coating layer 20 and a second coating layer 30 on the outer surface of the lithium-rich material, the chemical stability and air stability of the outside of the lithium-rich material are improved, thereby constructing another two protective layers; at the same time, the conductor particles 40 and the first coating layer 20 can play a synergistic role to achieve the purpose of suppressing the excessive internal resistance of the lithium-rich material and suppressing the excessive open circuit energy barrier of the battery.
[0052] In one implementation, please refer to Figure 2, the number of the conductor particles 40 is multiple, and the multiple conductor particles 40 are independently distributed on the outer surface of the core 10 to form an island-like coating, and the first coating layer 20 is combined between the multiple conductor particles 40 and connected to the outer surface of the core 10. Specifically, the outer surface of the lithium-rich material is combined with multiple independent conductor particles 40, and the multiple conductor particles 40 are distributed on the outer surface of the lithium-rich material in an "island-like" manner, and then the first coating layer 20 is filled on the outer surface of the lithium-rich material in an "ocean-like" manner. Therefore, on the outer surface of the lithium-rich material, the conductor particles 40 and the first coating layer 20 are combined to form an "island-like" structure.
[0053] In one embodiment, there are multiple conductor particles 40, and the multiple conductor particles 40 are continuously distributed on the outer surface of the lithium-rich material. Pores (including holes and / or gaps) are formed between at least some of the conductor particles 40, and the organic-inorganic hybrid material in the first coating layer 20 extends into the pores. Specifically, controlling the number of conductor particles 40 can make the multiple conductor particles 40 interconnected, and some pores are formed between the particles. Of course, it needs to be explained that the pores between the conductor particles 40 are only after the conductor particles 40 are made. It can be seen that after the first coating layer 20 is made, since the pores are filled, the pore structure cannot be directly obtained in the lithium-supplementing material.
[0054] In one implementation, please refer to Figure 2 , the particle size of the conductor particles 40 is greater than or equal to the thickness of the first coating layer 20, and the outer surface of at least part of the conductor particles 40 is connected to the second coating layer 30. Specifically, in the present application, the first coating layer 20 and the second coating layer 30 are both thin film layers, which need to be distinguished from the coating layers in the prior art. The first coating layer 20 and the second coating layer 30 are both obtained by liquid phase coating with a coupling agent, so the thickness of the first coating layer 20 and the second coating layer 30 is thin, and the first coating layer 20 and the second coating layer 30 have high density, and the conductor particles 40 are combined on the surface of the lithium-rich material by solid-state mixing, so the first coating layer 20 and the second coating layer 30 can be thinly covered on the surface of the conductor particles 40 and the lithium-rich material. The advantage of the thin first coating layer 20 and the second coating layer 30 is that it will not squeeze the lithium replenishment capacity of the lithium-rich material. In addition, the particle size of the conductor particles 40 is relatively large, so the first coating layer 20 and the second coating layer 30 can be bridged on the outer surface of the lithium-rich material through the conductor particles 40. The conductor particles 40 increase the specific surface area of the material, making the combination of the first coating layer 20 and the second coating layer 30 more stable.
[0055] In one implementation, please refer to Figure 3, the conductor particles 40 are bonded to the outer surface of the first coating layer 20, and the second coating layer 30 is bonded to the conductor particles 40. Optionally, there are multiple conductor particles 40, and the multiple conductor particles 40 are independently distributed on the outer surface of the first coating layer 20, and the second coating layer is bonded between the multiple conductor particles 40 and connected to the outer surface of the first coating layer 20.
[0056] It is understandable that the first coating layer 20 and the second coating layer 30 are made separately, so in the preparation process, the conductor particles 40 can be compounded first, and then the first coating layer 20 and the second coating layer 30 can be made separately. Of course, it is also possible to make the first coating layer 20 first, then compound the conductor particles 40 outside the first coating layer 20, and then make the second coating layer 30. The positions of the first coating layer 20 and the conductor particles 40 can be interchanged. Therefore, in the case where the first coating layer 20 is coated with lithium-rich material, the conductor particles 40 are connected to the outer surface of the first coating layer 20, and the conductor particles 40 can be distributed in the shape of "islands" on the outer surface of the first coating layer 20, and then the second coating layer 30 is combined with the conductor particles 40 or filled in the pores of the conductor particles 40. The advantage of this structure is that the conductor particles 40 are not only used to improve the interface stability, but also the conductor particles 40 bridge the first coating layer and the second coating layer 30 to achieve overall coating stability.
[0057] In one embodiment, in the lithium-supplementing material, the mass proportion of the organic-inorganic hybrid material is 0.2% to 2%, the mass proportion of the acid-inert material is 0.2% to 2%, and the mass proportion of the conductor particles 40 is 0.5% to 2%. Meeting the mass proportion of the organic-inorganic hybrid material, the acid-inert material and the conductor particles 40 within the above range can ensure the lithium-supplementing capacity of the lithium-supplementing material, reduce the surface residual alkali of the material and improve the density to significantly reduce the gas production due to high-temperature aging. When the proportion of lithium-rich material is too large, the removal of residual alkali on the surface of the lithium-rich material by the conductor particles 40 and the organic-inorganic hybrid material is weakened, and the protective effect of the first coating layer 20 and the second coating layer 30 becomes worse. When the proportion of lithium-rich material is too small, the lithium-supplementing capacity of the lithium-supplementing material decreases.
[0058] Optionally, the mass proportion of the organic-inorganic hybrid material can be 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%. The mass proportion of the acid-inert material is 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%. Optionally, the mass proportion of the conductor particles 40 is 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%.
[0059] In one embodiment, the thickness of the first coating layer 20 is 10nm-100nm. When the first coating layer 20 is within the above range, the stability of the lithium supplement material can be ensured, and the lithium ions can be fully released. When the thickness of the first coating layer 20 is too thin, the effect of the organic-inorganic hybrid material on eliminating the residual alkali on the surface of the lithium-rich material deteriorates, and the stability of the material deteriorates. When the thickness of the first coating layer 20 is too thin, the difficulty of lithium ion release increases, resulting in the lithium supplement capacity being affected. Optionally, the thickness of the first coating layer 20 can be 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm.
[0060] In one embodiment, the thickness of the second coating layer 30 is 10nm-100nm. When the thickness of the second coating layer 30 is within the above range, it can ensure the protection of the electrolyte components and resist the hydrofluoric acid in the battery. When the thickness of the second coating layer 30 is too thin, the effect of the acid-inert material in protecting the lithium-rich material and the electrolyte components becomes worse. When the thickness of the second coating layer 30 is too thin, the difficulty of lithium ion release increases, resulting in the lithium replenishment capacity being affected. Optionally, the thickness of the second coating layer 30 can be 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm.
[0061] In one embodiment, the particle size of the conductor particles 40 is 20nm-800nm. When the particle size of the conductor particles 40 is within the above range, the lithium replenishing capacity of the lithium replenishing material and the structural stability of the first coating layer 20 and the second coating layer 30 can be ensured. When the particle size of the conductor particles 40 is too small, the conductor particles 40 cannot play a bridging role. When the particle size of the conductor particles 40 is too large, the conductor particles 40 occupy the capacity of the lithium-rich material, and the compatibility of the conductor particles 40 and the lithium-rich material becomes poor. Optionally, the particle size of the conductor particles 40 can be 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm.
[0062] This application provides a method for preparing lithium supplement materials. Please refer to Figure 4 .
[0063] In one implementation, please refer to Figure 4 The preparation method of the lithium supplement material specifically comprises the following steps:
[0064] Step S10: Evenly mix the lithium-rich material and the organic-inorganic hybrid material precursor and sinter them, so that the organic-inorganic hybrid material is coated on the outer surface of the lithium-rich material to form a first coating layer.
[0065] Step S20, mixing the lithium-rich material having the first coating layer with the acid-inert material precursor and drying them, so that the acid-inert material is coated on the outer surface of the first coating layer to form a continuously coated second coating layer, thereby obtaining a lithium-supplementing material.
[0066] In one embodiment, in step S10, the type of lithium-rich material can refer to that provided in the above embodiment, which will not be repeated here. The organic-inorganic hybrid material precursor includes one or more of a phosphate coupling agent, a silane coupling agent, an aluminate coupling agent, a titanate coupling agent, and a chromium complex coupling agent. It should be explained that the coupling agent used in step S10 and the acid-inert material precursor used in step S20 may be the same or different. However, the products obtained in step S10 and step S20 are different, because the coupling agent needs to be sintered in step S10, so that the coupling agent is converted from an organic substance to an inorganic substance, that is, an organic-inorganic hybrid material is obtained. For example, after the silane coupling agent is sintered, silicon dioxide or silicon material can be obtained. The liquid phase coating method of coupling agent coating and sintering conversion is different from the conventional solid phase coating in the prior art. The obtained organic-inorganic hybrid material has higher density, that is, there are fewer gaps inside the material, and there are fewer gaps between the organic-inorganic hybrid material and the conductor particles, so that the organic-inorganic hybrid material has a more stable coating property for the lithium-rich material.
[0067] In one embodiment, in step S10, the lithium-rich material and the organic-inorganic hybrid material precursor are mixed in a mass ratio, and the amount of the organic-inorganic hybrid material precursor added can be 1%-5%, specifically 1%, 2%, 3%, 4%, 5%. The sintering temperature after mixing can be 600°C-800°C. The coupling agent is dispersed in the solvent, and as the solvent evaporates, it connects with the hydroxyl group on the surface of the lithium-supplementing material to form a stable coating layer, and under high-temperature sintering, an organic-inorganic hybrid film layer mainly composed of oxygen-silicon-oxygen bonds is formed. It plays a role in eliminating residual alkali on the surface of the lithium-supplementing material, reducing surface resistance, and reducing the erosion of water molecules.
[0068] It should be explained that by coating the first coating layer in a liquid phase coating manner, a smaller amount of organic-inorganic hybrid material precursor is used, thereby forming an "ocean-like" distribution of organic-inorganic hybrid materials on the surface of the lithium-rich material. On the one hand, a dense coating effect can be achieved, and on the other hand, the first coating layer formed can be prevented from being too thick and affecting the capacity of the lithium-supplementing material.
[0069] In one embodiment, in step S10, the lithium-rich material and the organic-inorganic hybrid material precursor are mixed evenly and sintered, specifically including: adding the lithium-rich material and the organic-inorganic hybrid material precursor to the solvent according to the mass ratio, and the mass ratio of the solute to the solvent is 1:20 to 2:5, stirring at high speed ultrasonic to form a mean dispersion, and placing it in an inert atmosphere for sintering after vacuum drying. The solvent is preferably a hydrophobic and lipophilic solvent, such as ethyl acetate, dimethyl carbonate, xylene, etc., and the solvent is selected as a reagent with a water content of less than 200ppm.
[0070] In one embodiment, in step S20, the acid-inert material precursor includes one or more of a phosphate coupling agent, a silane coupling agent, an aluminate coupling agent, a titanate coupling agent, and a chromium complex coupling agent. The amount of the acid-inert material precursor added can be 1%-5%, specifically 1%, 2%, 3%, 4%, and 5%. In this step, only the mixture needs to be dried without sintering treatment, so that the acid-inert material is retained in the outermost layer of the lithium supplement material. The drying temperature after mixing can be 60°C-70°C. Preferably, a silane coupling agent is used, which degrades to form an organic film layer mainly composed of oligosiloxane, which can well resist the erosion of trace water and hydrogen fluoride in the electrolyte, and the trace hydrolyzed organic film layer can also protect the electrolyte components, ultimately achieving the purpose of reducing battery gas production.
[0071] In one embodiment, before step S10, the following step is also included: compounding conductor particles on the surface of the lithium-rich material, please refer to Figure 4 :
[0072] Step S00, mixing the lithium-rich material and the conductor particles uniformly and sintering them, so that the conductor particles are bonded to the outer surface of the lithium-rich material.
[0073] In one embodiment, in step S00, the conductor particles include one or more of cobalt phosphate, iron phosphate, nickel phosphate, manganese phosphate, etc. Optionally, in a specific embodiment, the transition metal element in the conductor particles and the transition metal element in the lithium-rich material may be different, for example, the lithium-rich material may be lithium-rich lithium cobalt oxide, and the conductor particles may be iron phosphate. Through the sintering process, the metal elements in the conductor particles can be doped into the lithium-rich material, thereby doping the lithium-rich material, thereby reducing the gas production of the lithium-rich material and increasing the capacity of the lithium-rich material.
[0074] In one embodiment, in step S00, the lithium-rich material and the conductor particles are mixed in a mass ratio, and the amount of the conductor particles added can be 0.5% to 2%, preferably 1%; of course, in the case where step S00 is not performed, the mass of the conductor particles can be 0. The particle size of the mixed conductor particles is 200nm-1000nm, preferably cobalt phosphate. The cobalt phosphate and the residual alkali on the surface of the lithium-supplementing material react during high-temperature sintering at 600℃-800℃, and lithium phosphate and lithium cobalt compounds are generated at the surface junction, which eliminates part of the residual alkali and improves the bonding strength. In addition, lithium phosphate has good lithium ion conductivity, which helps to form a uniform lithium ion transport layer on the surface of the material. The lithium cobalt compound has good conductivity, and the coating can increase the wettability of the electrolyte, thereby reducing the interface charge transfer resistance and reducing side reactions.
[0075] It should be explained that, unlike the structure of completely coated conductor particles in the prior art, the lithium-rich material and conductor particles provided in the present application are mixed, and the content of conductor particles is relatively small, so that conductor particles distributed in an "island-like" manner can be formed on the surface of the lithium-rich material, which can fix the organic-inorganic hybrid material and acid-inert material behind it on the one hand, and can also play a role in reducing residual alkali on the other hand. At the same time, a small amount of conductor particles are mixed to avoid the coating layer formed being too thick and affecting the capacity of the lithium-supplementing material. The "island-like" distributed conductor particles can not only eliminate the residual alkali on the surface of the lithium-rich material, but also provide anchoring points for the coated coupling agent (organic-inorganic hybrid material), increase the contact area between the coupling agent and the lithium-rich material and the conductor particles, and thus improve the coating integrity of the coupling agent. At the same time, the organic-inorganic hybrid material obtained by sintering extends into the conductor particles distributed in an "island-like" manner, so that the first coating layer formed by the organic-inorganic hybrid material and the conductor particles together form a mutually engaged locking structure, thereby improving the coating strength of the first coating layer and improving the stability of the coating.
[0076] The present application can eliminate most of the residual alkali on the outer surface of the lithium-rich material by combining conductor particles on the outer surface of the lithium-rich material, and its conductor particles can form an "island-like" distribution, thereby forming anchor points, providing an attachment surface for the next step of coating the organic-inorganic hybrid material, and by sintering the coupling agent to form the organic-inorganic hybrid material, the stability of the material can be improved, and the electrical properties can be improved; and by repeatedly coating the coupling agent in the liquid phase on the outermost layer of the lithium-supplementing material to set the coupling agent, the lithium-rich material can be further protected, as well as the electrolyte components in the battery.
[0077] In one embodiment, the present application further provides a positive electrode material, the positive electrode material comprising a positive electrode active material and a lithium supplement. The lithium supplement is the lithium supplement material provided in the above embodiment. Optionally, the positive electrode active material can be a phosphate positive electrode active material or a ternary positive electrode active material. In a specific embodiment, the positive electrode active material comprises one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium vanadium phosphate fluoride, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0078] In one embodiment, the content of lithium-supplementing material in the positive electrode material can be controlled at 1% to 6% of the mass of the positive electrode active material. This ratio can just make up for the loss of active lithium in the battery during the first charging process. If the amount of lithium-supplementing material added to the positive electrode material is too low, the active lithium lost in the positive electrode active material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention rate of the battery. If the amount of lithium-supplementing material added to the positive electrode active material is too high, the original reversible capacity will be occupied and the cost will be increased. In some specific embodiments, in the positive electrode material, the mass percentage of the lithium-supplementing material can be 1%, 2%, 4%, 6%, etc.
[0079] In one embodiment, the present application further provides a positive electrode plate, the positive electrode plate comprising a current collector and an active material layer disposed on the current collector, the active material layer comprising the lithium supplement material of any one of the above embodiments. Or the active material layer comprises the lithium supplement material obtained by the preparation method of the lithium supplement material of the above embodiments.
[0080] In one embodiment, the positive electrode sheet includes a positive electrode current collector, and the positive electrode current collector has a positive electrode active layer, and the positive electrode active layer includes components such as positive electrode active materials, lithium supplement materials, conductive agents, and binders. The present application does not specifically limit these materials, and suitable materials can be selected according to actual application requirements. The positive electrode current collector includes but is not limited to any one of copper foil and aluminum foil. The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes, and the content of the conductive agent in the positive electrode active layer is 3wt% to 5wt%. The types of binders include polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive electrode active layer is 2wt% to 4wt%.
[0081] In one embodiment, the present application also provides a secondary battery, which includes a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode includes the above-mentioned positive electrode material; the electrolyte can be an electrolyte solution, so the secondary battery also includes a diaphragm arranged between the positive electrode plate and the negative electrode plate; or, the electrolyte can be a solid electrolyte solution, so the secondary battery does not have a diaphragm and is replaced by a solid electrolyte.
[0082] The technical solution of the present application is described in detail below through specific embodiments.
[0083] Example 1
[0084] This embodiment provides a lithium supplement material, please refer to Figure 5-Figure 8 The lithium-supplementing material includes a core of a lithium-rich material (Li6CoO4), as well as conductor particles (Co3(PO4)2), an organic-inorganic hybrid material and an acid-inert material (silane coupling agent), wherein the organic-inorganic hybrid material includes an O-Si-O bond and forms a first coating layer, and the acid-inert material forms a second coating layer.
[0085] The preparation method of the lithium supplement material comprises the following steps:
[0086] 1) Li6CoO4 and cobalt phosphate are uniformly mixed in a mass ratio of 97:1, and sintered at high temperature in an inert atmosphere so that cobalt phosphate forms an "island-like" structure on the surface of Li6CoO4, wherein the high-temperature sintering temperature is 700°C.
[0087] 2) The material obtained in step 1) and the silane coupling agent are added to the NMP solution at a mass ratio of 98:1, wherein the mass ratio of the solute to the solvent is 1:5. The dispersion is formed by high-speed ultrasonic stirring, and then vacuum-dried at 80°C and placed under high-temperature treatment in an inert atmosphere, so that the silane coupling agent is converted into an organic-inorganic hybrid film layer with oxygen-silicon-oxygen as the main body, and a "sea-like" structure is formed on the surface of Li6CoO4.
[0088] 3) The material obtained in step 2) and the silane coupling agent are added to the NMP solution in a mass ratio of 99:1, stirred under high-speed ultrasonic stirring to form a uniform dispersion, and dried under vacuum at 80° C. to obtain the lithium supplement material.
[0089] The mass ratio of lithium-rich material, cobalt phosphate, organic-inorganic hybrid material precursor (silane coupling agent) and acid-inert material precursor (silane coupling agent) is 97:1:1:1. The particle size of cobalt phosphate before mixing is 500nm, and the particle size of cobalt phosphate after high-temperature sintering is 370nm. The thickness of the first coating layer formed by the organic-inorganic hybrid material is 30nm, and the thickness of the second coating layer formed by the acid-inert material is 30nm.
[0090] in, Figure 5 is a transmission electron microscope image (TEM) of the lithium supplement material in Example 1; Figure 6 is a scanning electron microscope image (SEM) of the lithium supplement material in Example 1; Figure 7 is a scanning electron microscope (SEM) image of the lithium supplement material in Example 1 at another viewing angle; Figure 8 This is a scanning electron microscope (SEM) image of the lithium supplement material in Example 1 from another viewing angle. Figure 5-Figure 8 It can be seen that the lithium-replenishing material has a visible surface. The granular protrusions on the surface of the lithium-replenishing material are caused by the conductor particles, and the outermost layer of the lithium-replenishing material has an obvious coating layer structure (including organic-inorganic hybrid materials and acid-inert materials). Fig. 9 is the Raman image of the lithium-supplemented material of Example 1 and the lithium-rich material of Comparative Example 1; Fig.10 It is the infrared image of the lithium supplement material of Example 1 and the lithium rich material of Comparative Example 1.
[0091] Example 2
[0092] The present embodiment provides a lithium supplement material. The difference between the present embodiment and embodiment 1 is that the mass ratio of lithium-rich material, cobalt phosphate, organic-inorganic hybrid material precursor (silane coupling agent) and acid-inert material precursor (silane coupling agent) is 94:2:2:2, and cobalt phosphate is continuously distributed on the surface of Li6CoO4 without forming an "island-like" structure. The particle size of cobalt phosphate after high-temperature sintering is 440nm. The thickness of the first coating layer formed by the organic-inorganic hybrid material is 60nm, and the thickness of the second coating layer formed by the acid-inert material is 60nm.
[0093] Example 3
[0094] The present embodiment provides a lithium supplement material. The difference between the present embodiment and embodiment 1 is that the mass ratio of lithium-rich material, cobalt phosphate, organic-inorganic hybrid material precursor (silane coupling agent) and acid-inert material precursor (silane coupling agent) is 99.1:0.5:0.2:0.2. The particle size of cobalt phosphate after high-temperature sintering is 375nm. The thickness of the first coating layer formed by the organic-inorganic hybrid material is 30nm, and the thickness of the second coating layer formed by the acid-inert material is 10nm.
[0095] Example 4
[0096] This embodiment provides a lithium supplement material. The difference between this embodiment and embodiment 1 is that the particle size of the cobalt phosphate before mixing is 1000 nm, and the particle size of the cobalt phosphate after high-temperature sintering is 770 nm.
[0097] Example 5
[0098] This embodiment provides a lithium supplement material. The difference between this embodiment and embodiment 1 is that the particle size of the cobalt phosphate before mixing is 200 nm, and the particle size of the cobalt phosphate after high-temperature sintering is 100 nm.
[0099] Example 6
[0100] This embodiment provides a lithium-replenishing material. The difference between this embodiment and embodiment 1 is that the organic-inorganic hybrid material is coated on the outer surface of the lithium-rich material, and the cobalt phosphate is combined with the organic hybrid material. In the preparation method of the lithium-replenishing material: first perform step 2) to prepare the organic-inorganic hybrid film layer, and then perform step 1) to combine the cobalt phosphate.
[0101] Example 7
[0102] This embodiment provides a lithium supplement material. The difference between this embodiment and embodiment 1 is that the lithium supplement material only includes an organic-inorganic hybrid material and an acid-inert material. In the preparation method of the lithium supplement material: step 1 is not performed). The thickness of the first coating layer formed by the organic-inorganic hybrid material is 30 nm, and the thickness of the second coating layer formed by the acid-inert material is 30 nm.
[0103] Example 8
[0104] This embodiment provides a lithium supplement material. The difference between this embodiment and embodiment 1 is that the lithium-rich material is Li5FeO4 and the conductor particles are iron phosphate (FePO4).
[0105] Example 9
[0106] This embodiment provides a lithium supplement material. The difference between this embodiment and embodiment 1 is that a phthalate coupling agent is used in step 2).
[0107] Example 10
[0108] This embodiment provides a lithium supplement material. The difference between this embodiment and embodiment 1 is that both step 2) and step 3) use a phosphate coupling agent.
[0109] Comparative Example 1
[0110] This comparative example provides a lithium-rich material (Li6CoO4).
[0111] Comparative Example 2
[0112] This comparative example provides a lithium supplement material. The difference between this comparative example and Example 1 is that only a lithium-rich material and an acid-inert material are included. In the preparation method of the lithium supplement material: Step 1) and Step 2) are not performed.
[0113] Comparative Example 3
[0114] This comparative example provides a lithium supplement material. The difference between this comparative example and Example 1 is that it only includes lithium-rich material, cobalt phosphate and organic-inorganic hybrid material, and does not include acid-inert material. In the preparation method of the lithium supplement material: step 3) is not performed.
[0115] Comparative Example 4
[0116] This embodiment provides a lithium supplement material. The difference between this embodiment and embodiment 1 is that the lithium supplement material only includes cobalt phosphate and a silane coupling agent. In the preparation method of the lithium supplement material: in step 2), no high temperature treatment is performed, and the silane coupling agent is not converted into an organic-inorganic hybrid material.
[0117] The parameters of the lithium supplement materials provided by Examples 1 to 10 and Comparative Examples 1 to 4 are shown in Table 1:
[0118] Table 1 Parameters of lithium supplement materials provided in Examples and Comparative Examples
[0119]
[0120] The lithium supplement materials provided in the above-mentioned Examples 1 to 10 and the lithium supplement materials provided in Comparative Examples 1 to 4 are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:
[0121] Positive electrode sheet: The lithium supplement material, SP and PVDF are mixed in a mass ratio of 90:4:6 to prepare a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;
[0122] Negative electrode: lithium sheet;
[0123] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L;
[0124] Diaphragm: Polypropylene microporous separator;
[0125] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.
[0126] The lithium supplement materials, positive electrode sheets and lithium ion batteries prepared in the above Examples 1-10 and Comparative Examples 1-4 were tested as follows, and the test results are shown in Table 2 below:
[0127] 1) The specific surface area of lithium supplement materials is tested by the BET method.
[0128] 2) The resistance of the positive electrode is tested by a four-probe conductivity instrument.
[0129] 3) The lithium-ion battery is tested for overpotential and lithium replenishment capacity through electrochemical performance tests, and the test conditions are as follows: charging at a rate of 0.1C with a cut-off voltage of 4.3V; constant voltage charging at a cut-off of 4.3V; standing for 10 minutes after the charging process is completed, discharging at a rate of 0.1C with a cut-off voltage of 2.5V; observing the charging starting potential at the beginning of charging to obtain the starting overpotential of the lithium replenishment material; observing the charging platform during the charging process to obtain the decomposition voltage of the lithium replenishment material; and the first cycle efficiency = (charge specific capacity / discharge specific capacity)*100%.
[0130] 4) The gas production of lithium-ion batteries is tested by differential electrochemical mass spectrometry, and the test conditions are as follows: Assemble each lithium-supplementing material in accordance with the above-mentioned lithium-ion button battery assembly method, except that the positive and negative electrode shells of the button battery are hollow porous shells. Place the assembled battery into a sealed metal shell DMES gas production receiving device, and control the gas in and out only through capillaries. The above-mentioned gas-producing button battery is charged and discharged, and then connected to the DMES differential electrochemical mass spectrometer to test the gas production. External argon gas is used as a carrier gas and purge gas, and the gas produced in the battery formation stage is blown into the mass spectrometer for qualitative and quantitative analysis. In the same way, the gas production module is aged at high temperature and then connected to the mass spectrometer again to analyze the gas production results.
[0131] Table 2. Test results of embodiments and comparative examples
[0132]
[0133] It can be seen from the test results of Examples 1-10 and Comparative Example 1 in Table 2 that the total amount of gas produced by high-temperature aging of the lithium-supplementing materials of the examples prepared by the method provided in the present application is lower than that of the comparative examples. The lithium-supplementing material in Comparative Example 2 is only coated with a single layer of silane coupling agent and is not calcined, so Comparative Example 2 only has a weak effect of inhibiting gas production. The lithium-supplementing material in Comparative Example 3 is only coated with cobalt phosphate and organic-inorganic hybrid materials, so the effect of inhibiting gas production in Comparative Example 3 is improved, and through high-temperature sintering and the introduction of cobalt phosphate, further purification and the lithium cobalt compound at the interface of the solid-phase coating layer provide capacity, resulting in an increase in the lithium-supplementing capacity of the material. The lithium-supplementing material in Comparative Example 4 lacks a liquid-phase coating high-temperature treatment step, resulting in the outer layer of the lithium-rich material being composed only of solid-phase sintered cobalt phosphate and acid-inert materials. After the acid-inert material is partially degraded, the cobalt phosphate is a discontinuous coating layer, and the decomposition byproducts of the internal lithium-rich material come into contact with trace water and hydrogen fluoride to produce gas.
[0134] It can be seen from the test results of Examples 1-3 in Table 2 that by adjusting the mass proportion of each component, the thickness of each coating layer can be adjusted and the coating effect can be affected. When the proportion of conductive particles, organic-inorganic hybrid materials and acid-inert materials is too high, the gas production will be further reduced, but the lithium replenishment capacity will be reduced due to the decrease in the proportion of lithium-rich materials; when the proportion of conductive particles, organic-inorganic hybrid materials and acid-inert materials is too low, the gas production cannot be suppressed, and when the coating effect is poor, the lithium-rich materials are easily corroded by hydrofluoric acid and water vapor, resulting in the lithium replenishment capacity also being affected.
[0135] From the test results of Example 1 and Examples 4-5 in Table 2, it can be seen that the specific surface area of the lithium supplement material can be adjusted by adjusting the particle size of the conductor particles, thereby adjusting the material performance. When the particle size of the conductor particles is too large, the specific surface area of the lithium supplement material increases, and the electrode resistance does not decrease at this time. The possible reason is that the cobalt phosphate at the contact position between the conductor particles and the lithium supplement material is converted into lithium phosphate and lithium cobalt compounds, both of which have good electronic conductivity and ionic conductivity. The resistance of the material extending outward gradually increases, and the overpotential therefore also increases accordingly. In the case of a smaller particle size, better conductivity can be maintained.
[0136] It can be seen from the test results of Example 1 and Example 6 in Table 2 that the conductor particles can be located outside the first coating layer, and the purpose of suppressing gas generation can also be achieved. However, since the conductor particles are located outside the first coating layer, it is difficult for the conductor particles to combine with the lithium-rich material to generate lithium phosphate and lithium cobalt compounds, and no lithium ion transport layer is formed on the outer surface of the lithium-rich material, and the conductivity of electrons and ions deteriorates, resulting in an increase in the electrode sheet resistance and an increase in the overpotential, so the lithium replenishment capacity decreases.
[0137] From the test results of Example 1 and Example 7 in Table 2, it can be seen that due to the lack of support from the conductor particles, the specific surface area of the lithium replenishing material is greatly reduced, the delithiation energy barrier is greatly increased, the electrode resistance and overpotential increase seriously, and the lithium replenishing capacity is attenuated to a certain extent. However, due to the two coating layers formed by the organic-inorganic hybrid material and the acid-inert material, the total gas production of the battery during high-temperature aging is still maintained at a low level.
[0138] From the test results of Example 1 and Examples 8-10 in Table 2, it can be seen that the lithium-rich material is replaced with lithium-rich lithium ferrite, and the conductor particles are replaced with iron phosphate, and the lithium supplement effect and the gas production inhibition effect are verified. Replacing the silane coupling agent with other types of coupling agents can also achieve the purpose of inhibiting gas production, and the lithium supplement capacity can also be guaranteed. Therefore, it is shown that the solution provided in this application has strong applicability.
[0139] In summary, the present invention achieves the purpose of reducing battery gas production by coating the surface of lithium-rich materials with multiple layers of materials and by synergistic blending of the coating materials to improve the moisture resistance of the lithium-rich materials, resist corrosion from harmful components in the electrolyte, and improve the thermal stability of the electrolyte solvent.
[0140] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.
[0141] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. A lithium supplement material, characterized in that: It includes an inner core, a first coating layer and a second coating layer, wherein the first coating layer is coated on the outer layer of the inner core, and the second coating layer is coated on the outer layer of the first coating layer, the inner core includes a lithium-rich material, the first coating layer includes an organic-inorganic hybrid material, the second coating layer includes an acid-inert material, and the second coating layer is a continuous coating layer.
2. The lithium supplement material according to claim 1, characterized in that: The precursor of the organic-inorganic hybrid material includes a first coupling agent, the precursor of the acid-inert material includes a second coupling agent, and the density of the first coating layer is greater than the density of the second coating layer.
3. The lithium supplement material according to claim 1, characterized in that: The lithium supplement material further includes conductor particles, the conductor particles are bonded to the outer surface of the core, the first coating layer is bonded to the conductor particles, and the first coating layer and the conductor particles together fully coat the core.
4. The lithium supplement material according to claim 3, characterized in that: There are multiple conductor particles, and the multiple conductor particles are independently distributed on the outer surface of the inner core to form an island-shaped coating. The first coating layer is combined between the multiple conductor particles and connected to the outer surface of the inner core.
5. The lithium supplement material according to claim 4, characterized in that: The particle size of the conductor particles is greater than or equal to the thickness of the first coating layer, and at least a portion of the outer surface of the conductor particles is connected to the second coating layer.
6. The lithium supplement material according to claim 3, characterized in that: The mass proportion of the organic-inorganic hybrid material in the lithium supplement material is 0.2% to 2%; and / or The acid-inert material accounts for 0.2% to 2% by mass of the lithium-supplementing material; and / or The mass proportion of the conductor particles in the lithium supplement material is 0.5% to 2%; and / or The thickness of the first coating layer is 10nm-100nm; and / or The thickness of the second coating layer is 10nm-100nm; and / or The particle size of the conductor particles is 20nm-800nm.
7. A method for preparing a lithium supplement material, characterized in that: include: The lithium-rich material and the organic-inorganic hybrid material precursor are mixed evenly and sintered so that the organic-inorganic hybrid material is coated on the outer surface of the lithium-rich material to form a first coating layer; The lithium-rich material having the first coating layer is mixed with an acid-inert material precursor and dried so that the acid-inert material is coated on the outer surface of the first coating layer to form a continuously coated second coating layer, thereby obtaining a lithium-supplementing material.
8. The method for preparing the lithium supplement material according to claim 7, characterized in that: The lithium-rich material and the organic-inorganic hybrid material precursor are mixed uniformly and sintered, and the method further comprises: The lithium-rich material and the conductor particles are mixed uniformly and sintered so that the conductor particles are bonded to the outer surface of the lithium-rich material.
9. A positive electrode material, characterized in that: The positive electrode material comprises an active material and the lithium supplement material according to any one of claims 1 to 6, or comprises a lithium supplement material obtained by the preparation method of the lithium supplement material according to claim 7 or 8.
10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode and the negative electrode are arranged in the electrolyte, and the positive electrode comprises the positive electrode material according to claim 9.
Citation Information
Cited By
Conductive lithium supplement additive Li5FeO4 and preparation method thereof
CN120413830A
A single-phase, gassing-inhibited manganese-based positive electrode lithium supplement material and its preparation method and application
CN120413838B